Prevalence and risk factors of low back pain among commercial motorbike riders in Kathmandu Valley - Gautam, Roshani; Shrestha, Rejina (Nepal Medical College Journal, 2023)
Low back pain is a major health problem because of its high pre valence and has a consequence for disability and burden in the use of health services. It has a great impact on an individual’s economic productivity and quality of life. Motorbike riders are the vulnerable population for musculoskeletal disorders including low back pain. The objective of the study was to find out the prevalence and risk factors for low back pain among motorbike riders in Kathmandu Valley. An analytical cross sectional study was conducted in 265 commercial motorbike riders in Kathmandu. To collect data, convenience sampling technique and face to face interview was employed by using structured interview questionnaire. Data was analyzed in IBM SPSS software. Descriptive statistics and regression analysis was calculated. The study findings demonstrated that 43.8% of the respondents had low back pain among them 31.1% experienced more than 3 episodes of pain in last year. Similarly, 38% of the respondents had low back pain in last seven days. Low back pain is associated with BMI (p = 0.004), duration of commercial motorbike rides (p = 0.000), mileage per day (p = 0.002) and total riding hour per day (p = 0.001). It is concluded that nearly half of the commercial motorbike riders had low back pain in last one year and a significant association was found between low back pain with BMI, duration of commercial motorbike riding duration, riding mileage and riding hour per day. As commercial motorbike riding is a trending business, there should be some government regulations on working hours and other safety measures for the riders.